Mosquito-borne viruses causing human disease in Fennoscandia—Past, current, and future perspectives - Wilkman, Lukas; Ahlm, Clas; Evander, Magnus; Lwande, Olivia Wesula (Frontiers in Medicine, 2023)
Five different mosquito-borne viruses (moboviruses) significant to human disease are known to be endemic to Fennoscandia (Sindbis virus, Inkoo virus, Tahyna virus, Chatanga virus, and Batai virus). However, the incidence of mosquito-borne virus infections in Fennoscandia is unknown, largely due to underdiagnosing and lack of surveillance efforts. The Fennoscandian moboviruses are difficult to prevent due to their method of transmission, and often difficult to diagnose due to a lack of clear case definition criteria. Thus, many cases are likely to be mis-diagnosed, or even not diagnosed at all. Significant long-term effects, often in the form of malaise, rashes, and arthralgia have been found for some of these infections. Research into mobovirus disease is ongoing, though mainly focused on a few pathogens, with many others neglected. With moboviruses found as far north as the 69th parallel, studying mosquito-borne disease occurring in the tropics is only a small part of the whole picture. This review is written with the objective of summarizing current medically relevant knowledge of moboviruses occurring in Fennoscandia, while highlighting what is yet unknown and possibly overlooked.